Mathematics Teacher's Response to Blended Learning Hyper content with Hyperlinks as a Limited Face-to-Face Learning Strategy - Turmudi Turmudi; Asep Syarif Hidayat; Widayanti Widayanti; Aan Yuliyanto; Riska Nurhasanah; Ahmad Rizal Jalaludin; Nana Diana (Didaktik Matematika, 2022)
The need for adaptive learning strategies during limited face-to-face learning inspires this study. The research intends to analyze the responses and implementation plans of mathematics teachers in implementing blended learning hyper content with hyperlinks on linear equation system with two variables (LESTV). The data collection was done through survey involving questionnaires and interview sheets. Data were then analyzed descriptively. The participants were 38 mathematics junior high teachers in Purwakarta, Indonesia. This study shows the enthusiasm and confidence of teachers in implementing blended learning hyper content with hyperlinks, which is undoubtedly a new insight. It is deemed flexible and easy to apply and becomes an alternative during limited face-to-face learning. Mathematics teachers can plan Blended Learning Hyper content with Hyperlinks through various media and topics. Various LESTV problem-solving strategies can give student interest in studying LESTV concepts and solving problems.